IMPLEMENTASI MODEL CONTEXTUAL TEACHING AND LEARNING BERBASIS ETNOMATIKA GHUMAH BOSA UNTUK MENINGKATKAN LITERASI DAN NUMERASI MATEMATIS SISWA - Nurhayati Lubis; Syahriani Sirait (Universitas Islam Sumatera Utara, 2026)
This study aims to determine the effect of the Contextual Teaching and Learning model based on Malay culture on students’ mathematical numeracy literacy abilities in the topic of flat-sided geometric solids for grade VIII students at UPTD SMP Negeri 3 Silau Laut in the 2025/2026 academic year. This study used a quasi-experimental method with a two-group pretest-posttest design. The population of this study consisted of all grade VIII students at UPTD SMP Negeri 3 Silau Laut, while the sample consisted of two classes selected using purposive sampling techniques, namely the experimental class and the control class. The experimental class was taught using the Malay culture-based Contextual Teaching and Learning model assisted by the GeoGebra application, while the control class used the expository learning model. Data collection techniques included mathematical numeracy literacy tests, observation, and documentation. Data analysis was carried out using normality tests, homogeneity tests, and hypothesis tests. The results showed that the implementation of the Malay culture-based Contextual Teaching and Learning model had an effect on students’ mathematical numeracy literacy abilities. Students in the experimental class showed improvement in analyzing information, using mathematical symbols, performing arithmetic operations, and interpreting problem-solving results compared to students in the control class. In addition, learning integrated with Malay culture and the use of the GeoGebra application were able to increase students’ learning motivation, activeness, and understanding of mathematical concepts in a more contextual and meaningful way. Therefore, the Malay culture-based Contextual Teaching and Learning model is effective as an alternative mathematics learning model to improve students’ mathematical numeracy literacy abilities.